Mother-Daughter Enmeshment: An Analysis of Lisa See’s Novel Shanghai Girls (International Journal of Food and Nutritional Sciences, 2022)
Lisa See is a Chinese-American writer, who has focuses on the mother-daughter relationship, female friendship, and sisterhood in her writings. Lisa See spins the story with history and cultures of China. Mother-Daughter relationship is unique and it describes the thing that goes between the mother and the daughters. The novel Shanghai Girls represent twentieth century Chinese traditional mother and the modern daughters. The paper is analysed based on the feminist theorist Sara Ruddick three concepts of maternal thinking. This paper brings out the care and love of a mother towards her daughter through various incidents that highlighted in the novel.